Competency of SPI Members in Improving the Quality of Supervision Performance at Manado State University - Miran, Michael (Budapest International Research and Critics University, 2022)
Internal Supervision within the Ministry of Education and Culture as set in Regulation of the Minister of Education and Culture Number 22 of 2017 has tasks and functions help Head of Work Unit in to do internal control with organize function preparation of supervision programs supervision policies and programs. Characteristic study descriptive is the collected data in the form of words, pictures and not numbers All collected possibly Becomes key to what already researched the data possible originated from script interview notes field photo videotape, documentation private notes or memos, and documents official other. Based on the results and discussions that have been researcher describe about Competence Member Spi In frame Enhancement Quality of Supervision Performance at Manado State University then researcher take conclusion as That competencies needed by SPI UNIMA in To do Duty supervision is competence in the field of Management Source Power People Finance and goods state property with discipline Science Management Law, Accounting and Engineering, amount SPI members should be odd and have amount more of 12 people. Training sustainable required in develop competence. Selection competence and record footsteps required in recruitment member Spi. Giving honors and rewards every assignment and execution Duty, and then competence leader in to do coordination and arrangement assignment supervision.